Assessment of efficiency of application of high spinal anesthesia in the operations on upper part of abdominal cavity - A. N. Plekhanov (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
Authors of the given work develop a technique of high spinal anaesthesia in the operations on the upper part of abdominal cavity, and also conduct the assessment of its efficiency and safety at the operations. Experience of performance of 112 operations is presented. The given way of one-stage high spinal anaesthesia allows to achieve the high neuromuscular block to level of the 1-2nd thoracic vertebras. Time introductions anaesthetics in volume to 5 -10 ml. makes (on the average) 1 - 2 minutes that allows to create high degree of turbulence of an entered solution and as promotes distribution of vortical streams in cranial a direction liqour spaces for the purpose of distribution anaesthetics further from an injection place. In the early postoperative period anaesthesia was not required from patients narcotic analgetics. Complications in a kind: headaches, a nausea, vomiting, temperature it has not been noted. Complications from operative intervention it was not marked. In article it is shown that high spinal anaesthesia has considerable advantages before other kinds of anaesthesia, in particular before endotrachea a narcosis. It is easier transferred by the patient, does not cause terrible complications.